Fenologi Tajuk Pohon Mahoni (Swietenia macrophylla King) di Areal UNSRAT - Nepi Tabuni; Hard N. Pollo; J. S. Tasirin (COCOS, 2017)
ABSTRACT  Temporal variation in canopy phenology of Mahogany Tree (Swietenia macrophylla King) is a general pnenomenon that happened in field plantations.  Seasonal timing in case of early - late shoot emergence, leaf shading, flower emergence, and fruit maturation are life cycle events that can be used to predict flowering patterns and reproductive success.  Mahogany tree vegetation in UNSRAT area is one of isolated population that interested to be considered.    The aims of this research was to study temporal variation in canopy phenology of Mahogany Tree.  The researh was done by Cencus Method from May to June 2017.  The data were analysed by using descriptive statistics.  The result showed that from the 346 tree visually observed, there are 134 trees have new shoot emergence,  189 trees have young leaves, 26 trees have yellow color leaves for shading, 4 trees in stage of flowering emergence, 82 trees in fruiting stage, 6 trees has fallen fruits, and 1 tree has contain young fruit.  These imply that the canopy phenology of mahagony tree has high variation in response to its ambient condition.  Keywords : Mahogany Tree, canopy phenology, temporal variation, seasonal timing, UNSRAT